Rule 1a[edit | edit source]

xa * xb = xa+b

Example[edit | edit source]

y3 * y10 = y10+3 = y13

ie

y*y*y * y*y*y*y*y*y*y*y*y*y = y13

Rule 1b[edit | edit source]

xa / xb = xa-b

Example[edit | edit source]

y65 / y40 = y65-40 = y25

Rule 2[edit | edit source]

( xa)b = xab

Example[edit | edit source]

( m5)1/5 = m5*1/5 = m

Rule 3[edit | edit source]

x0 = 1

Proof[edit | edit source]

x1 / x1 = 1 (anything divided by itself = 1)

and x1 / x1 = x0 (rules 1b)

Therefore x0 = 1

Community content is available under CC-BY-SA unless otherwise noted.